Harnessing the Chemistry of the Indole Heterocycle to Drive Discoveries in Biology and Medicine. (17th July 2019) - Norwood, Verrill M.; Huigens, Robert W.
Abstract: Indole‐containing compounds demonstrate an array of biological activities relevant to numerous human diseases. The biological activities of diverse indole‐based agents are driven by molecular interactions between indole agent and critical therapeutic target. The chemical inventory of medicinally useful or promising indole compounds spans the entire structural spectrum, from simple synthetic indoles to highly complex indole alkaloids. In an analogous fashion, the chemistry behind the indole heterocycle is unique and provides rich opportunities for extensive synthetic chemistry, enabling the construction and development of novel indole compounds to explore chemical space. This review will present heterocyclic chemistry of the indole nucleus, indole compounds of clinical use, complex indole alkaloids and indole‐inspired discovery efforts by multiple research groups interested in using novel indole‐containing small molecules to drive discoveries in human biology and medicine. Abstract : Not so indolent : Indole‐containing compounds demonstrate an array of biological activities relevant to human disease. The indole nucleus provides rich opportunities for synthetic chemistry by enabling construction and development of novel compounds for exploration. This review presents chemistry of the indole heterocycle and programs aimed at utilizing new indole‐containing molecules to drive discoveries.